New concepts for interpretation of intracoronary velocity and pressure tracings. Issue 5 (November 1995) - Di Mario, C.; Gil, R.; Sunamura, M.; Serruys, P. W.
Abstract : The development of quantitative angiography and the introduction of new imaging techniques cannot replace functional methods of assessing the severity of stenosis. Measurement of transstenotic pressure gradient and poststenotic flow velocity using miniaturised sensors with guidewire technology offers an alternative to the conventional non-invasive methods that is immediately applicable in the catheterisation laboratory during interventional procedures. The complexity of the coronary circulation, however, makes it difficult to establish simple cut-off criteria to identify the presence of a flow-limiting stenosis. For intermediate lesions or in the presence of variable haemodynamic conditions, the accuracy of the assessment can be improved by the application of more complex indices proposed and validated in the laboratory animals. Two of these indices are myocardial fractional flow reserve and the slope of the instantaneous relation between pressure or pressure gradient and flow velocity.